การตรวจสอบความเที่ยงตรงของผลการออกรางวัลสลากกินแบ่งรัฐบาลโดยใช้การทดสอบไคกำลังสอง - พานิชกิจโกศลกุล, วราฤทธิ์ (Thai Journal of Science and Technology, 2013)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อตรวจสอบความเที่ยงตรงของผลการออกรางวัลสลากกินแบ่งรัฐบาล โดยใช้การทดสอบไคกำลังสองซึ่งเป็นการทดสอบการแจกแจงของหมายเลขต่าง ๆ ที่เกิดขึ้นในแต่ละหลักของรางวัลที่ 1 รางวัลเลขท้าย 3 ตัว และรางวัลเลขท้าย 2 ตัว โดยศึกษาใน 2 ช่วงเวลา คือ ระหว่างงวดประจำวันที่ 16 มกราคม 2546 ถึง 16 กุมภาพันธ์ 2556 (จำนวน 243 งวด) และระหว่างงวดประจำวันที่ 1 ตุลาคม 2549 ถึง 16 กุมภาพันธ์ 2556 (จำนวน 154 งวด) ผลการวิจัยสรุปได้ว่าในระหว่างงวดประจำวันที่ 16 มกราคม 2546 ถึง 16 กุมภาพันธ์ 2556 ผลการออกรางวัลที่ 1 และรางวัลเลขท้าย 3 ตัว ครั้งที่ 1 ไม่เที่ยงตรง ที่ระดับนัยสำคัญ 0.05 และผลการออกรางวัลเลขท้าย 2 ตัว เที่ยงตรง ที่ระดับนัยสำคัญ 0.05 ส่วนระหว่างงวดประจำวันที่ 1 ตุลาคม 2549 ถึง 16 กุมภาพันธ์ 2556 ผลการออกรางวัลที่ 1 และรางวัลเลขท้าย 3 ตัว ครั้งที่ 4 ไม่เที่ยงตรง ที่ระดับนัยสำคัญ 0.05 และผลการออกรางวัลเลขท้าย 2 ตัว เที่ยงตรง ที่ระดับนัยสำคัญ 0.05 คำสำคัญ : สลากกินแบ่งรัฐบาล; การทดสอบไคกำลังสอง; ความเที่ยงตรง Abstract The objective of this research is to examine the accuracy of government lottery results by using chi-square test. The chi-square test is used to test the distribution of each number occurs of the first prize, three-digit-last prize and two-digit-last prize. Testing consider government lottery results occurred in two periods: January 16, 2003 thru February 16, 2013 (the total of 243 times) and October 1, 2006 thru February 16, 2013. Results of the research are as follows. In during January 16, 2003 thru February 16, 2013, government lottery results of the first prize and three-digit-last prize in the first game are not accuracy with a significance level of 0.05. Further, government lottery results of two-digit-last prize are accuracy with a significance level of 0.05. In during October 1, 2006 thru February 16, 2013, government lottery results of the first prize and three-digit-last prize in the fourth game are not accuracy with a significance level of 0.05. Further, government lottery results of two-digit-last prize are accuracy with a significance level of 0.05. Keywords: government lottery; chi-square test; accuracy